PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEMANFAATAN, KEAMANAN DAN SIKAP PENGGUNAAN TEKNOLOGI TERHADAP KEPUTUSAN PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) (STUDI EMPIRIS PADA UMKM DI KOTA AMBON) - Linggi, Marchantia; Atawarman, Rita; Risakotta, Kathleen Asyera (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
This research aims to determine the effect of perception of ease, perception of usefulness, security and attitude to use of technology on decisions to use quick response code indonesian standard (qris) in micro, small and medium enterprises. This research uses quantitative methods. The object of this research is MSME players in Ambon City who are using QRIS. This study uses primary data, namely through a questionnaire using a Likert scale and used a sample of 100 respondents. The results of this study indicate that perceived conveniencehas no significant effect on the decision of MSME actors to use QRIS, this is evidenced by the t test which gets a significance value of 0.557> 0.05. This is because there are still problems with the application of QRIS. This is because there are still problems with the QRIS application. Perceived usefulness has a positive and insignificant influence on the decisions of MSME actors in using QRIS. This is evidenced by the partial test results whose significance value is 0.195> 0.05. QRIS is very helpful for digital payment systems for MSME players in Ambon City. Security has a positive and significant influence on the decision of MSME players to use QRIS, this is evidenced by the t test which gets a significant value of 0.000> 0.05. The attitude of using technology has a positive and significant influence on the decision of MSME players to use QRIS. Where the significance value is 0.003> 0.05. The better the attitude felt by MSME players in Ambon City, the higher the decision to use QRIS.